DEVELOPMENT OF REGIONAL TOURISM RESOURCES: CURRENT OPPORTUNITIES AND PROSPECTS (American Journal of Business Management, Economics and Banking, 2025)
Regional tourism resources, including natural, cultural, and historical objects, are an important component of the tourism industry. These resources play a significant role in developing the region's economy, increasing employment, and preserving the national heritage. This article analyses the existing potential of regional tourism resources and their future development prospects.